2019
DOI: 10.1186/s12917-019-1801-4
|View full text |Cite
|
Sign up to set email alerts
|

Renal shear wave elastography and urinary procollagen type III amino-terminal propeptide (uPIIINP) in feline chronic kidney disease

Abstract: BackgroundChronic kidney disease (CKD) is one of the most common diseases occurring in cats. It is characterized by renal fibrosis, which is strongly correlated with impairment of renal function. Since renal biopsy is not performed routinely in clinical practice, the non-invasive method of ultrasonographic shear-wave elastography (SWE) was used to determine renal parenchymal stiffness. Currently, urinary procollagen type III amino-terminal propeptide (uPIIINP) is a renal fibrosis biomarker in humans. Moreover,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
22
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(41 citation statements)
references
References 57 publications
15
22
1
Order By: Relevance
“…[ 24 ] were reported that using K/Ao is a suitable method for considering renal size in dogs. Our results corresponded with the previous studies in both dogs and cats [ 32 , 51 , 52 ], all of which suggest decreased that renal size is an important indicator in evaluation of CKD progression [ 24 , 51 - 53 ].…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…[ 24 ] were reported that using K/Ao is a suitable method for considering renal size in dogs. Our results corresponded with the previous studies in both dogs and cats [ 32 , 51 , 52 ], all of which suggest decreased that renal size is an important indicator in evaluation of CKD progression [ 24 , 51 - 53 ].…”
Section: Discussionsupporting
confidence: 92%
“…Age, gender, breed, bodyweight, and BCS had no significant effect on the renal E values of either cortex or medulla in this study, consistent with the previous findings in canine [ 43 ], feline [ 32 ], and human [ 63 ]. However, the small number of animals included in this study is one of the important limitations in evaluating the influence of demographic variables on SWE.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations